ALTERITY AND EMPATHY IN POST-1945 ASIAN AMERICAN NARRATIVES - Park, Hyesu.
1 online resource (1 volume)
Keywords: This book examines how Asian American authors since 1945 have deployed the stereotype of Asian American inscrutability in order to re-examine and debunk the stereotype in various ways. By paying special attention to what narrative theorists have regarded as one of the most extraordinary aspects of fiction--its ability to give (or else deny) readers a remarkably detailed knowledge of the inner lives of their characters--this book explores deeply and systematically the specific ways Asian American narratives attribute inscrutable minds to Asian American characters, situating them at various points along a spectrum stretching between alterity and empathy. Ultimately, the book reveals the link between narrative form and larger cultural issues associated with the representation of Asian American minds, and how a nuanced investigation of narrative form can yield insights into the sociocultural embeddedness of Asian American literature under the case studies--insights that would not be available if such formal questions were by passed.